1997
DOI: 10.1037/0735-7044.111.5.873
|View full text |Cite
|
Sign up to set email alerts
|

Impaired trace eyeblink conditioning in bilateral, medial-temporal lobe amnesia.

Abstract: Trace eyeblink classical conditioning was assessed in patients with bilateral medial-temporal amnesia and matched control participants who had previously shown equivalent delay eyeblink conditioning (J. D. E. Gabrieli et al., 1995). The silent trace interval varied for durations of 500, 750, or 1,000 ms in successive sessions separated by at least 2 weeks; extinction trials followed each session. Patients with amnesia produced significantly fewer conditioned responses (CRs) than did control participants at all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
139
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 191 publications
(148 citation statements)
references
References 63 publications
6
139
1
Order By: Relevance
“…In delay eyeblink conditioning, the CS and US overlap and coterminate. Trace eyeblink conditioning shares several features with declarative memory, most notably the fact that learning depends on the hippocampus (Clark & Squire, 1998;McGlinchey-Berroth, Carrillo, Gabrieli, Brawn, & Disterhoft, 1997) and on awareness of the stimulus contingencies (Clark & Squire, 1998;Manns, Clark, & Squire, 2000a, 2000b. In contrast, delay eyeblink classical conditioning appears to be a quintessential example of nondeclarative memory.…”
mentioning
confidence: 99%
“…In delay eyeblink conditioning, the CS and US overlap and coterminate. Trace eyeblink conditioning shares several features with declarative memory, most notably the fact that learning depends on the hippocampus (Clark & Squire, 1998;McGlinchey-Berroth, Carrillo, Gabrieli, Brawn, & Disterhoft, 1997) and on awareness of the stimulus contingencies (Clark & Squire, 1998;Manns, Clark, & Squire, 2000a, 2000b. In contrast, delay eyeblink classical conditioning appears to be a quintessential example of nondeclarative memory.…”
mentioning
confidence: 99%
“…This finding that was later confirmed by Moyer, Deyo and Disterhoft (1990) who demonstrated that acquisition was eliminated using a 500 ms trace interval (but not a 300 ms trace interval) with rabbits who had relatively complete hippocampectomies. Similarly, our In our original study, we speculated two possible sources of the impaired learning observed in amnesic patients: residual hippocampal function leading to some preserved declarative memory or intact cerebellar function that, when given enough practice, can acquire some level of trace conditioning via procedural learning (McGlinchey-Berroth, Carrillo, Gabrieli, Brawn, & Disterhoft, 1997). The current study is an attempt to distinguish between these two possibilities.…”
mentioning
confidence: 72%
“…laboratory has demonstrated impaired trace conditioning in humans using a 500 ms silent trace period in amnesic patients with bilateral medial temporal lobe damage, and little if any acquisition as the trace interval was extended to 1000 ms (McGlinchey-Berroth, Carrillo, Gabrieli, Brawn, & Disterhoft, 1997). Similarly, Woodruff-Pak (1993) demonstrated impaired acquisition in two amnesic patients (one being the patient H.M.), although both eventually achieved criterion performance with additional training.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These patients acquire eyelid conditioning at a normal rate when a delay paradigm is used (e.g., Weiskrantz & Warrington, 1979). However, acquisition is impaired when a trace paradigm is used and this impairment is more severe the longer the trace interval (McGlinchey-Berroth, 1997). This impairment seems to be specific to the discontinuity between the CS and the US in the trace procedure, given that patients who showed impaired acquisition with a 600 ms trace interval showed, however, perfect conditioning with a 750 ms delay procedure (Gabrieli, McGlinchey-Berroth, Carrillo, & Gluck, 1995).…”
Section: Human Eyelid Conditioningmentioning
confidence: 97%